Analisis Pengaruh Aliran- Aliran Filsafat pada Kehidupan Sehari-hari - Devi, Shinta Prasetia; Winarno, Agung (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Philosophy has long been an integral part in shaping human thought patterns and behavior. However, in the context of everyday life, the influence of philosophical schools is often hidden in the moral, social and individual decisions we make. This research aims to analyze how various philosophical schools, such as rationalism, empiricism, existentialism, pragmatism, analytical philosophy, and moral philosophy, influence everyday life through a systematic literature review. By collecting and analyzing scientific articles, books and related research, this research assesses the practical application of philosophical principles in aspects of human life, from individual ethics to social and political impacts. The findings of this study show that philosophical schools contribute significantly to the formation of views of life, ethical decision making, and social relationships. However, its implementation often faces challenges in the complex context of modern life. This research suggests the importance of understanding philosophy in improving the quality of personal and societal life. Apart from that, this study also opens up space for further research regarding the role of philosophy in the context of technology and globalization